2004
DOI: 10.1364/ol.29.001974
|View full text |Cite
|
Sign up to set email alerts
|

Photonic crystal fiber based evanescent-wave sensor for detection of biomolecules in aqueous solutions

Abstract: Abstract:We demonstrate evanescent-wave sensing of Cy5-DNA-molecules in an aqueous solution using a photonic crystal fiber. Less than 0.8pL sample volume placed in the holes of the fiber is sufficient for reliable detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
151
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(159 citation statements)
references
References 6 publications
2
151
0
3
Order By: Relevance
“…7,14 LPFGs can thus be used for biochemical sensing based on the evanescent-wave detection principle. [151][152][153][154][155] As shown in Fig. 21, a promising biochemical sensor based on a LPFG written in a PCF by a CO 2 laser has been demonstrated to detect the average thickness of a layer of biomolecules within a few nm.…”
Section: F Biochemical Sensorsmentioning
confidence: 99%
“…7,14 LPFGs can thus be used for biochemical sensing based on the evanescent-wave detection principle. [151][152][153][154][155] As shown in Fig. 21, a promising biochemical sensor based on a LPFG written in a PCF by a CO 2 laser has been demonstrated to detect the average thickness of a layer of biomolecules within a few nm.…”
Section: F Biochemical Sensorsmentioning
confidence: 99%
“…It has been shown that photonic crystal fibers can be used for evanescent-wave sensing of biomolecules, such as DNA [14] or proteins [15]. These experiments were done using labelled biomolecules, where each target molecule carries a fluorescent tag.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-based fluorescence sensing has been deployed in sensing targets such as: aluminum ions [7], hydrogen peroxide [8], oxygen [9], and explosives [10]. Optical fiber based fluorescence sensors have also been deployed for biological applications, including measurements of biomolecules in solution [11], DNA [12], or enzyme assays within microstructured fibers [13].…”
Section: Introductionmentioning
confidence: 99%